PERTIMBANGAN HAKIM TERHADAP PENETAPAN DISPENSASI PERKAWINAN DI PENGADILAN AGAMA KOTA SUKABUMI TAHUN 2019 - Iswandi, Saida Nurfadila (AS-SALAM, 2019)
This article aims to describe the Judge's Consideration of the Determination of Marriage Dispensation at the Sukabumi City Religious Court in 2019. One of the requirements for marriage is the minimum age limit in accordance with Article 7 paragraph (1) of Law No. 16 of 2019 which states that "marriage is only permitted if men and women have reached the age of 19 (nineteen) years ". The method used is a qualitative approach method using a normative juridical research approach. This research examines the basis on what is used by the judge in granting permission for dispensation of marriage. The results of this study explain that the Judge uses PERMA Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Applications as a basis in deciding and granting cases of marriage dispensation. There are several forms of determination regarding the dispensation of marriage in the Sukabumi religious court, including the dispensation given to prospective brides whose age is still below the minimum age to have a marriage, dispensations given to prospective grooms whose age is still below the minimum age to have a marriage, granting marriage dispensation to underage women who are already pregnant, refusing or not being granted a marriage dispensation request. The positive contribution expected from this article is the dedication of the community to the minimum age limit for marrying with the aim of forming a harmonious and quality family.